Rapid disappearance of left ventricular mass (presumed thrombus) in a patient with cardiomyopathy. Issue 3 (March 1982) - Bensaid, J; Blanc, P; Virot, P
Abstract : A man aged 41 years with a clinical diagnosis of cardiomyopathy and hepatic insufficiency was found, on angiocardiography, to have a mass, presumably a thrombus, within the left ventricle. A second angiocardiogram performed five days later showed that the thrombus had disappeared. The mechanism invoked was more probably an increase of spontaneous fibrinolysis as described in cirrhotic patients, perhaps helped by heparin, rather than ejection of the mass from the ventricle with silent embolisation somewhere in the systemic circulation.